COMMUNICATION ACCOMMODATION STRATEGIES IN JOE BIDEN’S ELECTION ACCEPTANCE & VICTORY SPEECH - Rahadigama, I Putu Pandu (Udayana Journal of Social Sciences and Humanities; Vol 7 No 2 (2023): Vol 7 No 2 (2023): UJoSSH, September 2023, 2024)
This study is entitled COMMUNICATION ACCOMMODATION STRATEGIES IN JOE BIDEN’S ELECTION ACCEPTANCE & VICTORY SPEECH. The aims is to identify the types of communication accommodation strategy are used by Joe Biden in his election acceptance & victory speech and the reason behind the usage of each strategies based on theory by Giles about Communication Accommodation Theory. The data was taken Joe Biden’s Election Acceptance and Victory Speech. The data was collected by documentation method. In analyzing data, the method applied is qualitative method. The data was presented in in the form of sentence using descriptive method. The results show that there were nine divergence strategies and twelve convergence strategies being used in Joe Biden’s speech. Convergence in Joe Biden’s speech is mainly used when he seek for the approval from his audiences, such as addressing his supporters by each social groups that they’re in, and using certain expressions in delivering his message to relate to the people. Meanwhile, by using divergence, Biden created a situation where people would listen to him mentioning about the achievements, the hardwork, and the pledge that he and the other notable individuals have under their name.